Review of Daniel Goldmark. 2005. Tunes for ‘Toons: Music and the Hollywood Cartoon. Berkeley and Los Angeles: University of California Press - McQuiston, Kate (Current Musicology, 2006)
Daniel Goldmark’s monograph, the first on music in cartoons, will interest both a popular and scholarly readership. Tunes for ‘Toons offers lively description, analysis, and history, and it makes a tremendous contribution to the scholarly literature by illuminating the working processes and creative tendencies of composers, as well as by unpacking the codes and systems behind cartoons that use familiar classical music and others that use jazz. Goldmark’s attention to the industry of animation, his effective use of documentary materials, and his evident enthusiasm for the subject all enhance his work. Useful to anyone interested in the hows and whys of cartoon scoring (especially fans of Merrie Melodies and Tom and Jerry), the book provides rich analyses of individual cartoons, and these interpretations serve as models for understanding other undiscussed cartoons.